Acoustic simulation of a patient's obstructed airway. Issue 2 (25th January 2016) - van der Velden, W.C.P.; van Zuijlen, A.H.; de Jong, A.T.; Lynch, C.T.; Hoeve, L.J.; Bijl, H.
Abstract : This research focuses on the numerical simulation of stridor; a high pitched, abnormal noise, resulting from turbulent airflow and vibrating tissue through a partially obstructed airway. Characteristics of stridor noise are used by medical doctors as indication for location and size of the obstruction. The relation between type of stridor and the various diseases associated with airway obstruction is unclear; therefore, simply listening to stridor is an unreliable diagnostic tool. The overall aim of the study is to better understand the relationship between characteristics of stridor noise and localization and size of the obstruction. Acoustic analysis of stridor may then in future simplify the diagnostic process, and reduce the need for more invasive procedures such as laryngoscopy under general anesthesia. In this paper, the feasibility of a coupled flow, acoustic and structural model is investigated to predict the noise generated by the obstruction as well as the propagation of the noise through the airways, taking into account a one-way coupled fluid, structure, and acoustic interaction components. The flow and acoustic solver are validated on a diaphragm and a simplified airway model. A realistic airway model of a patient suffering from a subglottic stenosis, derived from a real computed tomography scan, is further analyzed. Near the mouth, the broadband noise levels at higher frequencies increased with approximately 15–20 dB comparing the stridorous model with the healthy model, indicating stridorous sound.